Innovative bridge deck solutions: Examining the impact response and capacity of UHPC with FRP stay-in-place formworks - Pournasiri, Emad; Pham, Thong; Hao, Hong (2024)
This study investigates the impact behaviour of bridge decks constructed with ultra-high-performance concrete (UHPC) and fibre-reinforced polymer (FRP) stay-in-place (SIP) formwork. Eight scaled bridge decks were fabricated and tested under pendulum impacts. Two different FRP SIP formwork configurations, i.e., square hollow section (SHS) and Y-shaped stiffened, were considered. Two types of reinforcing bars, i.e., steel and glass FRP (GFRP), were adopted for these samples. The influence of impact velocity on the transient response and progressive damage of the concrete decks under impact loading was investigated. The test results showed that UHPC and Y-shaped stiffeners were effective in decreasing the peak and residual displacements of decks by up to 70 % when compared to decks made with normal strength concrete. UHPC and Y-shaped stiffeners greatly improved the impact and residual impact capacities. The use of GFRP rebars instead of steel reinforcement changed the failure mode and FRP SIP formwork reduced deck damage and mitigated scabbing failure under impact loads. The configuration of FRP SIP formwork had a substantial influence on the impact force and thus the deck's performance. Especially, this study has observed an interesting phenomenon under impact, i.e., reaction force could be greater than impact force, which has not been reported in the literature yet.